Relationship between Investor Sentiment and Price Fluctuation of SSE 50ETF Options. (29th June 2022) - Wang, Yang; Zhang, Yinjie; Fu, Yuwei
Abstract : In this paper, we have studied the December call-options contract of SSE 50ETF options to put forward the sentiment composite index of options by means of the principal component analysis and to explore the relationship between such index and the fluctuation taking place in option prices. The empirical study has shown that the investor sentiment is correlated with option prices, and option prices prove to be more sensitive to the sentiment, whereas the impact imposed by the sentiment of option investors on option prices is more significant.